Applications of noncovariant gauges in the algebraic renormalization procedure - Boresch, A (World Scientific, 1998)
Includes bibliographical references (p. 139-144) and index; This volume is a natural continuation of the book Algebraic Renormalization, Perturbative Renormalization, Symmetries and Anomalies, by O Piguet and S P Sorella, with the aim of applying the algebraic renormalization procedure to gauge field models quantized in nonstandard gauges. The main ingredient of the algebraic renormalization program is the quantum action principle, which allows one to control in a unique manner the breaking of a symmetry induced by a noninvariant subtraction scheme. In particular, the volume studies in-depth the following quantized gauge field models: QED, Yang–Mills theories and topological models (the Chern–Simons and the BF model) in the context of axial-like gauges.